2004
DOI: 10.1002/pc.20048
|View full text |Cite
|
Sign up to set email alerts
|

UV aging of poly(propylene)/wood‐fiber composites

Abstract: The effect of accelerated UV‐aging on properties of PP/wood‐fiber composites has been studied. Plates containing 0, 25 and 50 wt% wood‐fibers were subjected to accelerated UV‐aging in a QUV weatherometer for up to 8 weeks. Stabilization against UV‐degradation was made by adding 3% of a UV stabilizer. The results showed that both the unfilled PP and the PP/wood‐fiber composites displayed good UV resistance with regard to mechanical properties. The color of the PP/wood‐fiber composite plates changed from brown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 14 publications
7
91
0
1
Order By: Relevance
“…Crazing of WPC may be caused by polymer chain scission, which results in highly crystallized polymer zones that crack and/or differentially contract (resulting from wetting and drying cycles) between the surface and interior sections during xenon-arc and exterior weathering. Surface cracks occurred around 400 h, and their frequency and size increased upon extended weathering, findings that are in agreement with the literature [12,31]. Densification of surface layers and spontaneous cracking of weathered PP may result from the scission of tie chain molecules in the amorphous phase that are released and then crystallized onto pre-existing crystals (a process known as chemicrystallization) [31].…”
Section: Visual Appearance and Surface Crackingsupporting
confidence: 73%
See 2 more Smart Citations
“…Crazing of WPC may be caused by polymer chain scission, which results in highly crystallized polymer zones that crack and/or differentially contract (resulting from wetting and drying cycles) between the surface and interior sections during xenon-arc and exterior weathering. Surface cracks occurred around 400 h, and their frequency and size increased upon extended weathering, findings that are in agreement with the literature [12,31]. Densification of surface layers and spontaneous cracking of weathered PP may result from the scission of tie chain molecules in the amorphous phase that are released and then crystallized onto pre-existing crystals (a process known as chemicrystallization) [31].…”
Section: Visual Appearance and Surface Crackingsupporting
confidence: 73%
“…The color changed from brown to chalky white, with the depth of degradation being approximately 0.5 mm. Seldé n et al [12] also reported that the degradation of the PP matrix resulted in a chalky appearance and extensive surface cracking. Falk et al [13] observed that PP-based composites faded at a higher rate than HDPE-based composites.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The FTIR spectra of WF, HDPE, HDPE with 2% MAPE, and unweathered control samples of WF/HDPE composites are shown in Figure 3. Because the maleated coupling agents had no significant influence on the degradation of WPC, 16 its effect was not discussed here.…”
Section: Ftir Spectroscopymentioning
confidence: 98%
“…Peaks that appear in the spectra can be assigned to functional groups present at the composite surface. Thus, Oxidation at the degraded surface can be detected throughout weathering (Matuana et al 2001;Muasher and Sain 2006;Stark et al 2004a;Selde´n et al 2004;Colom et al 2000).…”
Section: Introductionmentioning
confidence: 98%